Fatty acid and lipid profiles in primary human trophoblast over 90 h in culture. (June 2017) - Ferchaud-Roucher, Véronique; Rudolph, Michael C.; Jansson, Thomas; Powell, Theresa L.
Abstract: Little is known about the mechanisms underlying the preferential transport of long chain polyunsaturated fatty acids (LCPUFA) to the fetus by the syncytiotrophoblast and the role of cytotrophoblasts in placental lipid metabolism and transport. We studied primary human trophoblast (PHT) cells cultured for 90 h to determine the fatty acid and lipid composition of cytotrophoblast (18 h culture) and syncytiotrophoblast (90 h culture) cells. In cultured PHT total lipid fatty acids were significantly ( P < 0.05) reduced at 90 h compared to 18 h in culture including lower levels of palmitic acid (PA, 16:0, −37%), palmitoleic acid (POA, 16:1n-7, −30%), oleic acid (OA, 18:1n-9, −31%), LCPUFA arachidonic acid (AA, 20:4n-6, −28%) and α-linolenic acid (ALA, 18:3n-3, −55%). In major lipid classes, OA and most of the n-3 and n-6 LCPUFA were markedly lower at 90 h in TG (−57 to −76%; p < 0.05). In the cellular NEFA, n-6 LCPUFA, dihomo-γ-linolenic acid (DGLA, 20:3n-6) and AA were both reduced by −51% and DHA was −55% lower ( p < 0.05) at 90 h. In contrast, phospholipid FA content did not change between cytotrophoblasts and syncytiotrophoblast except for OA, which decreased by −62% ( p < 0.05). Decreasing PHT TG and NEFA lipid content at 90 h in culture is likely due to processes related to differentiation such as alterations in lipase activity that occur as cytotrophoblast cells differentiate. We speculate that syncytiotrophoblast prioritizes PL containing AA and DHA for transfer to the fetus by mobilizing FA from storage lipids. Highlights: Differentiation of primary human trophoblast cells in culture is accompanied by changes in fatty acid content. Syncytiotrophoblast have decreased fatty acids in storage forms such as triglycerides compared to cytotrophoblast cells. Syncytiotrophoblast prioritize synthesis of phospholipids containing LCPUFA, likely for transfer to the fetal circulation.